Patents and innovation: Why is government policy for one so badly out of alignment with the other? - Calhoun, Doug (New Zealand Science Review, 2012)
​The then Minister of Science, Dr Wayne Mapp, announced in July 2009 that his top priority was to enhance the migration of science from the laboratory to the marketplace. On his watch we saw the 2010 CRI Taskforce Report recommend that technology transfer should become a core responsibility of CRIs: CRIs should develop, invest in and manage intellectual property (IP) and get it off their balance sheets. In his swan song, Dr Mapp launched the report commissioned by the Ministry of Science and Innovation, ‘Powering Innovation’. That report recommended ways to improve access to and uptake of R & D in the high-value manufacturing and services sector (HVMSS). High-quality technology transfer was again seen as a critical factor. The Patents Act 1953 is about to be replaced by an updated Patents Bill. Midway through 2012, the new law had been through several iterations of public consultation, and scrutiny by a select committee, and was awaiting its second reading. You would be entitled to think that patent policy would be aligned with innovation policy. But you would be looking for any link between the two in vain. At the heart of the patent policy is the observation that about 90% of New Zealand patents are granted to foreigners. The benefits of these may flow overseas. Therefore, we should make it as difficult as possible to get a patent. The Patents Bill will bring more rigorous examination of patent applications, more opportunities to attack patents and the exclusion of patents for certain technologies. The excluded technologies are among those identified as being HVMSS technologies.